(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article describes the goals and tasks of forming spiritual values among young people in New Uzbekistan. In this area, conclusions are given based on the decisions of the President of the Republic of Uzbekistan and the decisions of the Cabinet of Ministers. Also, in the article, issues of formation of such qualities as loyalty to the motherland, entrepreneurship, willpower, ideological immunity, kindness, responsibility, culture, innovative thinking, hard work in young people are highlighted.